Environmental pollution and human exposure to polycyclic aromatic hydrocarbons in the east Baltic region - Hemminki, Kari; Veidebaum, Toomas (Scandinavian Journal of Work, Environment & Health, 1999)
Environmental contamination by polycyclic aromatic hydrocarbons (PAH) and human exposure were surveyed in the east Baltic region. Polluted and heavily industrialized areas are upper Silesia in Poland, northern Bohemia in the Czech Republic, and the northeast part of Estonia. In Estonia the pollution is in a defined geographic area, where lung cancer incidence is higher than elsewhere. In Silesia, exposure of some 5 million people appears to be elevated; DNA (deoxyribonucleic acid) adduct levels in white blood cells are increased in groups of residents with apparently only environmental exposure. By extrapolation, some 150 annual lung cancer cases could be predicted due to PAH in Silesia. Air levels of benzo[a]pyrene were increased in northern Bohemia, and domestic heating and power plants using brown coal appeared to be major contributors to particulate air pollution in winter. Further studies are needed to assess health risks of PAH exposure in central and eastern Europe.
Keywords: cancer risk; dna adducts; environmental contamination; extrapolation; pollution; unit risk